E|Benchmark - A pioneering method for energy efficient process planning and assessment along the life cycle process - Kreitlein, Sven; Schwender, Sabrina; Rackow, Tobias; Franke, Jörg (Procedia CIRP, 2015)
This paper introduces a method for the assessment and evaluation of energy efficiency of the manufacturing processes in the production from the perspective of production planning. Production planning is an organizational entity within an enterprise and deals with the creation and provision of all production relevant documents and equipment in order to achieve maximum efficiency through a minimum of resources and effort. The tasks of production planning are evaluated by means of their relevance for an energy efficiency comparison. For this, evaluation criteria are determined that consider influences on the production processes and basic goals of production. This is necessary due to the fact that tasks of production planning cannot be evaluated directly via energy consumption and energy efficiency. This results in 12 tasks through which a high leverage effect for a more energy efficient production can be achieved. Another possibility for an energy efficiency evaluation is presented via the approach of minimal value calculation. The underlying concept is the comparison and evaluation of energy efficiency based on the ratio of the theoretically required energy consumption to the actual energy consumption. By linking the minimum value calculation to the production planning, a predetermination of the theoretical energy consumption - And thus an energy efficient planning - is possible. The resulting energy saving potentials extend over the entire life cycle of a process and enable savings of an increasing energy amount.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Energy efficiency; Process forward-planning; Sustainable manufacturing

Green factories Bavaria: A network of distributed learning factories for energy efficient production - Kreitlein, Sven; Höft, Annika; Schwender, Sabrina; Franke, Jörg (Procedia CIRP, 2015)
The Green Factory Bavaria project contributes to the ability of Bavarian companies to improve their resource consumption. The main impulses include the knowledge transfer of applied research in the industry and the organization of experience exchange among companies. Therefore, Bavarian-wide so-called Green Factories for energy-efficient production are being developed and expanded, see, for instance, the learning and research platforms at the Technische Universitát in Munich, the Friedrich-Alexander-University Erlangen-Núrnberg as well as at Universities of Applied Sciences in Amberg/Weiden, Ansbach, Coburg, Hof, Nuremberg, and Schweinfurt/Wúrzburg. Together, universities and companies are developing technical solutions and methodological approaches for the reduction of resource consumption and are presenting the latest Green Factories findings, where theoretical training can be made comprehensible through demonstration. The companies are supported through individual consulting services, while internet-based checklists and benchmarking analyzes help to determine the need for action. At each location specific Bavarian-wide coordinated technology priorities as well as cross-cutting issues are presented. Joint activities are processed, thereby ensuring the exchange of information among the institutions as well as with the industry. In the model factories for energy-efficient manufacturing innovative industrial partners shall receive the opportunity to demonstrate advanced techniques and technologies for energy-efficient production in the available laboratory and production areas, develop hand-in-hand with scientists from the participating research institutions, build a network among themselves, and circulate the findings effectively to users and students.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Energy-efficient production; Interdisciplinary research-groups; Knowledge exchange